Chloride Ion Transport by the E. coli CLC Cl−/H+ Antiporter: A Combined Quantum-Mechanical and Molecular-Mechanical Study - Wang, Chun-Hung; Duster, Adam W.; Aydintug, Baris O.; Zarecki, MacKenzie G.; Lin, Hai (Frontiers in Chemistry, 2018)
We performed steered molecular dynamics (SMD) and umbrella sampling simulations of Cl– ion migration through the transmembrane domain of a prototypical E. coli CLC Cl–/H+ antiporter employing combined quantum-mechanical (QM) and molecular-mechanical (MM) calculations. The SMD simulations revealed interesting conformational changes of the protein. While no large-amplitude motions of the protein were observed during pore opening, the side chain rotation of the protonated external gating residue Glu148 was found critical to full access of the channel entrance by Cl–. Moving the anion into the external binding site (Sext) induced small-amplitude shifting of the protein backbone at the N-terminal end of helix F. As Cl– travelled through the pore, rigid-body swinging motions of helix R separated it from helix D. Helix R returned to its original position once Cl– exited the channel. Population analysis based on polarized wavefunction from QM/MM calculations discovered significant (up to 20%) charge loss for Cl– along the ion translocation pathway inside the pore. The delocalized charge was redistributed onto the pore residues, especially the functional groups containing pi bonds (e.g. the Tyr445 side chain), while the charges of the H atoms coordinating Cl– changed almost negligibly. Potentials of mean force computed from umbrella sampling at the QM/MM and MM levels both displayed barriers at the same locations near the pore entrance and exit. However, the QM/MM PMF showed higher barriers (~10 kcal/mol) than the MM PMF (~2 kcal/mol). Binding energy calculations indicated that the interactions between Cl– and certain pore residues were overestimated by the semi-empirical PM3 Hamiltonian and underestimated by the CHARMM36 force fields, both of which were employed in the umbrella sampling simulations. In particular, CHARMM36 underestimated binding interactions for the functional groups containing pi bonds, missing the stabilizations of the Cl– ion due to electron delocalization. The results suggested that it is important to explore these quantum effects for accurate descriptions of the Cl– transport.